2020
DOI: 10.1128/mra.00468-20
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of SARS-CoV-2 in a Tiger from a U.S. Zoological Collection

Abstract: This report describes the identification and characterization of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in a Malayan tiger in a U.S. zoo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 4 publications
1
96
0
1
Order By: Relevance
“…For example, restricting contact and access to at-risk species in marine parks could help protect captive marine mammals. Such an approach has been suggested to protect other susceptible species including lions and tigers, following the reverse zoonotic infection of a tiger with SARS-CoV-2 at the Bronx Zoo in New York ( Wang et al, 2020b ). Similarly, non-human primate Old world apes and monkeys are also predicted to be highly susceptible to SARS-CoV-2 and these findings have led to improved measures for protecting these primates at zoos ( Melin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, restricting contact and access to at-risk species in marine parks could help protect captive marine mammals. Such an approach has been suggested to protect other susceptible species including lions and tigers, following the reverse zoonotic infection of a tiger with SARS-CoV-2 at the Bronx Zoo in New York ( Wang et al, 2020b ). Similarly, non-human primate Old world apes and monkeys are also predicted to be highly susceptible to SARS-CoV-2 and these findings have led to improved measures for protecting these primates at zoos ( Melin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The transmission of the SARS-CoV-2 virus from humans to other vulnerable species in proximity to humans has already been observed. In a New York Public zoo, a critically endangered tiger and several other animals (including lions) were infected with the SARS-CoV-2 virus ( Wang et al, 2020b ). When the perpetrator virus was sequenced from a sick Malayan tiger, it was revealed that it was two strains of human origin (i.e, two separate human-feline transmission events) that had infected these feline species ( McAloose et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…SPI1), IRFs, and NF-κB1/2 in the promoter of regions of IL-6 and ACE2 gene orthologs [50][51][52][53][54][55][56]. We extracted the primal promoter sequences from IL-6 and ACE2 genes from 25 representative vertebrate species, which contain ten previously validated SARS-CoV2-susceptible species and other naturally unsusceptible species based on collected evidence [26][27][28][29][30]. As shown in Figure 3, all three types of CREs (i.e.…”
Section: Cross-species Comparison Of Key Cis-regulatory Elements (Crementioning
confidence: 99%
“…The largest difference is between phylogenic positions of IL-6 and ACE2 gene promoters for pigs and guinea pigs. Whereas in the IL-6 promoter phylogeny, the pig sisters to those of the alpaca and horse, within the Carnivore clade that contains most of the validated CoV2(+) species in addition to the primate clade, porcine ACE2 gene promoter was next to the ruminant clade that has no CoV2(+) species identified so far [20][21][22][23][24][25][26][27][28][29]. Guinea pig as a rodent species has its IL-6 promoter surprisingly within the primate clade, but its ACE2 promoter appears more primitive and shares the clade with the frog.…”
Section: Overall Comparison Of Phylogenic Topologies Between Il-6 Andmentioning
confidence: 99%
See 1 more Smart Citation